Inspire Challenge Award: Seeing is believing – Using smartphone camera data - CGIAR Platform for Big Data in Agriculture (2018)
This project integrates machine-learning analysis of cellphone camera images of crops into the functioning of an insurance and farm advisory service. Early results from a RCT demonstrated advisory messages, which reached 32,237 wheat producers, increased knowledge on best agricultural practices by 78 percent.